Animal assisted brief therapy : a solution-focused approach - Pichot, Teri. (New York, NY : Routledge, 2012)
'This book provides therapists with concrete examples of how to appropriately implement Animal Assisted Activities/Therapy (AAA/T) to cultivate positive effects in treatment. It explains how this loving and patient therapy for clients need not be the difficult challenge that it at first appears to be. This resource takes you step by step through the process, showing what practical strategies can be used to offset most obstacles and unknowns. This one-of-a-kind guide clearly explains how to blend and structure the numerous aspects of AAA/T with Solution Focused Therapy to become a more effective treatment program. Appendices provide AAA/T resources, sample policy and procedures, and training resources across the United States. Animal-Assisted Brief Therapy: A Solution-Focused Approach provides a comprehensive look at AAA/T and is perfect for therapists struggling to find new and effective ways to work with clients; therapists trying to utilize this approach in their practice; administrators and clinical supervisors wanting to implement AAA/T at their agency; educators; and students'--
'This book provides a comprehensive look at AAA/T and is perfect for therapists struggling to find new and effective ways to work with clients; therapists trying to utilize this approach in their practice; administrators and clinical supervisors wanting to implement AAA/T at their agency; educators; and students'--
Includes bibliographical references and index.
Keywords: Pets -- Therapeutic use; Animal-assisted therapy; Solution-focused brief therapy